Drawing up indicators regarding success in public health programmes having a social-sports approach (2010)
evaluated so as to draw up and develop indicators of success regarding social programmes’ efficacy and effectiveness. Method This was a descriptive survey. The sample consisted of 51 participants, male (n=29) and female (n=22), from the Nova Descoberta project whose ages ranged from 8 to 17. Data was obtained from a semi-directed survey having open items covering 10 topics; it was carried out with children and adolescents over a 2-year period (2007-2008). Documental data was also obtained from schools which had agreed to cooperate with the project. Results There were no statistically significant differences (p